Moral Boundaries and Cultural Membership: Perceptions of the LGBTQ in Turkiye - Murat Ergin; Fatoş Gökşen (Journal of Economy Culture and Society)
Sexual minorities consistently rank as the most disapproved of group in Turkey although the LGBTQ community remain largely invisible. To explain this disparity, we examine private and public responses to “homosexuality” along four dimensions: demographic factors, social context, religion and religiosity, and public morality. The data come from a nationally representative survey (N=1893). We tested four sets of variables to explain the persistence of mistrust toward sexual minorities. The first two, demographic factors and social context, show limited explanatory power. The third dimension of personal morality is also limited, because boundaries against LGBTQ individuals also cut across religion and religiosity. The fourth dimension, public morality, a vision of moral values shaping public life and political discourse, explains the particularity of the views toward non-straight sexual orientations as the specific alignment of a moral worldview with exclusionary cultural membership. Results are significant in two ways. First, they show that the mistrust of sexual minorities is high. Second, the public displays of mistrust are different from the forms of prejudice expressed toward other groups, such as ethnic minorities. The symbolic boundaries drawn vis-àvis LGBTQ individuals tells us more about the core values of belonging and solidarity in Turkish society.